How Physicochemical Parameters of Water Change with Distance in a Lake: Case Study Lake Bunyonyiinkigezi - Mukasa-Tebandeke, I. Z.; Karume, I.; Ssebuwufu, J.; Wasajja, H.Z; Nankinga, R; Kansiime, Z. (International Journal of Advances in Chemistry (IJAC), 2021)
Pollution resulting from unsustainable agricultural and urbanization activities in the Ruhezamyenda and Bunyonyi catchments are threatening lake Bunyonyi. These have led to high chemical oxygen demand (COD), electrical conductivity, turbidity, pH, iron (II) concentration and low dissolved oxygen (DO5). In this study we have investigated the how COD, turbidity, pH, concentration of iron, total suspended solids, total nutrients and DO5 of water changed with distance in lake. Water sampled from different distances in the lake filtered using Whatman paper at ambient temperatures was tested for COD, electrical conductivity, turbidity, total nutrients, iron, hardness and DO5. COD was 20.8±.0.03mg/L to 16 ± 0.03mg/L; total hardness was 16.5±0.2 mg/L to 18.6 ± 0.3 mg/L total nitrate was 103.5± 2 mg/L to 88 ± 3 mg/L; total phosphate was 100.8 ±.2.5 to 87± 3 mg/L; high TSS values from 3.4 ± 0.1 mg/L to 2.5 ± 0.1 mg/L showed contamination of water. As pH decreased from 8.3 ± 0.03 to 7.6 ± 0.04 revealed that bases were getting removed. The turbidity dropped from 25.7 ± 0.3 NTU to 20 ± 2 NTU due settling down of sediments. Iron (II) concentration ranging from 1.1± 0.1 to 0.8± 0.1 mgL-1. Dissolved oxygen decreased from 7.9 ±0.3 mg/L to 4.8 ± 0.2 mg/L indicating surface water can uphold life of aquatic organisms. Total hardness ranged from 0.22± 0.05 to 0.19± 0.05 mg/L Electrical conductivity was high and ranged from 130± 5 to 150± 5 µS/cm indicating presence of electrolytes. Lake Bunyonyi water is not greatly polluted, but requires to be safe guarded against poor unsustainable agricultural practices, sewage draining from towns, schools and hotels in nearby settlements.